Lifestyle behaviors and ethnic identity among diverse women at high risk for type 2 diabetes. (July 2016) - Brown, Susan D.; Ehrlich, Samantha F.; Kubo, Ai; Tsai, Ai-Lin; Hedderson, Monique M.; Quesenberry, Charles P.; Ferrara, Assiamira
Abstract: Background: Diet and physical activity lifestyle behaviors are modifiable risk factors for type 2 diabetes and are shaped by culture, potentially influencing diabetes health disparities. Objectives: We examined whether ethnic identity—the strength of attachment to one's ethnic group, and a long-standing focus of psychological research—could help account for variations in lifestyle behaviors within a diverse population at high risk for chronic disease. Methods: Using data from the Gestational Diabetes' Effects on Moms trial, this US-based cross-sectional study included 1463 pregnant women (74% from minority ethnic/racial groups; 46% born outside the US) with gestational diabetes (GDM), a common pregnancy complication conferring high risk for type 2 diabetes after delivery. Mixed linear regression models examined whether ethnic identity is associated with lifestyle behaviors after adjusting for demographic, clinical, and acculturative characteristics (e.g., nativity and length of residence in the US). Results: In the overall sample, a one-unit increase in ethnic identity score was significantly associated with 3% greater fiber intake, 4% greater fruit/vegetable intake, 11% greater total activity, and 11% greater walking ( p values < 0.01). Within ethnic/racial groups, a one-unit increase in ethnic identity score was significantly associated with 17% greater fiber intake among Filipina women; 5% lower total caloric intake among non-Hispanic White women; and 40% greater total activity, 35% greater walking, and 8% greater total caloric intake among Latina women ( p values ≤ 0.03). Conclusion: Results from this large study suggest that ethnic group attachment is associated with some lifestyle behaviors, independent of acculturation indicators, among young women with GDM who are at high risk for type 2 diabetes. Stronger ethnic identity may promote certain choices known to be associated with reduced risk of type 2 diabetes. Prospective research is needed to clarify the temporal nature of associations between ethnic identity and modifiable diabetes risk factors. Highlights: Gestational diabetes is common and confers high risk for type 2 diabetes. Diet and physical activity are modifiable diabetes risk factors shaped by culture. Ethnic identity was associated with some diet and activity lifestyle behaviors. Associations varied across diverse ethnic/racial groups. Research should explore causal links among ethnic identity and lifestyle behaviors.